Economic freedom and interventionism : an anthologi of articles and essays - Mises, Ludwig Von 1881-1973; Bien Greave, Bettina (New York : The Foundation for Economic Education, 1990)
<Intervencionismo>
Keywords: ECONOMIA; MISES, LUDWIG VON (1881-1973); LIBERALISMO ECONOMICO; LIBERALISMO